What is the relationship between body mass index and reaction speed in PPLOP boxing athletes in Central Java? - Islam, Syahrizal; Husein, Muhamad; Abadi, Akabar Kusuma; Pratama, Okky Putra Alwin; Nubatonis, Jefrio Demitrimus; Kristiono, Aljawahir Agus; Dewi, Indah Sari; Wijaya, Muhammad Budi; Salacup, Vince Louisse D. (Universitas Tanjungpura, 2024)
Background and Study Aim. Boxing requires an optimal balance between body weight and reaction speed. Body Mass Index (BMI) is a common measure used to assess body composition. For boxers, maintaining weight within the optimal range is crucial for peak performance. Additionally, reaction speed is a key skill in boxing; the ability to quickly respond to an opponent